Preparation method of MOFs (Metal-Organic Frameworks)-based solid electrolyte membrane for sodium-ion battery

By using the preparation method of MOFs-based solid electrolyte membrane in sodium ion batteries, the problems of flammability and poor thermal stability of liquid electrolytes are solved, and the safety and service life of the battery are improved.

CN119627205AActive Publication Date: 2025-03-14ZHEJIANG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411745811.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-14
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The liquid electrolytes in existing sodium ion batteries have problems such as flammability, leakage and poor thermal stability, which affect the safety and service life of the battery.

Method used

Using the preparation method of a MOFs-based solid electrolyte membrane, a MOFs crystal is formed by reacting a soluble zinc salt with 2-methylimidazole in a solvent, and then doping it with an ionic liquid and forming a thin film by coating to form a MOFs-based solid electrolyte membrane doped with an ionic liquid.

Benefits of technology

It improves the ionic conductivity and electrochemical stability of sodium ion batteries, reduces the risk of leakage, and improves the safety and service life of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of sodium ion batteries, in particular to a preparation method of an MOFs (Metal-Organic Frameworks)-based solid electrolyte membrane for a sodium ion battery, which comprises the following steps: 1) dissolving soluble zinc salt in a solvent I, adding 2-methylimidazole for dissolving, and crystallizing; washing and baking the obtained MOFs crystal; (2) adding the obtained MOFs particles into an ionic liquid solvent, and uniformly dispersing; then separating, suspending the separated solid precipitate in acetone again, and taking the obtained turbid liquid as a coating liquid; and 3) uniformly coating a pre-cleaned substrate with the coating liquid to form a thin film, then carrying out drying and heat treatment, and finally, separating the thin film from the substrate to obtain the MOFs-based solid electrolyte membrane. Through reasonable design and optimization, the overall performance of the sodium-ion battery is improved, and reliable technical support is provided for practical application of the sodium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion batteries, and in particular to a method for preparing a MOFs-based solid electrolyte membrane for sodium ion batteries. Background Art

[0002] With the continuous increase in global energy demand and the increasingly serious environmental problems, the development of clean and sustainable energy storage technology has become a research hotspot in the current scientific and technological field. Lithium-ion batteries have been widely used in portable electronic devices and electric vehicles due to their high energy density and long cycle life. However, the limited and uneven distribution of lithium resources make lithium-ion batteries face challenges in large-scale energy storage applications. Therefore, finding a substitute for lithium ions has become an urgent problem to be solved. In this context, sodium-ion batteries have gradually become the focus of research due to their abundant sodium resources, wide distribution and low cost.

[0003] The basic principle of sodium-ion batteries is similar to that of lithium-ion batteries, and the storage and release of electrical energy are mainly achieved through the embedding and de-embedding of sodium ions. The core components of sodium-ion batteries include positive electrode materials, negative electrode materials and electrolytes. Among them, compared with positive and negative electrode materials, the research on electrolytes of sodium-ion batteries is relatively lagging. As an indispensable component of sodium-ion batteries, the main function of electrolytes is to conduct sodium ions, and they also need to have high ionic conductivity, good electrochemical stability and a wide voltage window. At present, sodium-ion batteries mainly use liquid electrolytes. In 2024, the patent (CN118248948A) of Henan Penghui Power Co., Ltd. reported that a sodium-ion battery of a layered oxide / hard carbon system was prepared by using non-aqueous organic solvents, sodium salts and additives as electrolytes. The battery can maintain a capacity retention rate of more than 91.51% after 200 cycles, and a capacity retention rate of more than 87.28% after 400 cycles. However, there are some problems with liquid electrolytes that cannot be ignored, such as flammability, easy leakage, poor thermal stability, etc., which seriously affect the safety and service life of sodium-ion batteries. Therefore, the development of solid electrolytes with high safety and high stability has become an important research direction for sodium-ion batteries.

[0004] Metal-organic framework compounds (MOFs) are a class of porous materials composed of metal ions or metal clusters and organic ligands through coordination bonds. They have large specific surface area, rich pore structure and adjustable chemical functions. MOFs are applied to solid electrolytes of sodium ion batteries. Their porous structure can effectively improve the conductivity of sodium ions. At the same time, the adjustability of their structure also provides the possibility of optimizing electrolyte performance. Yu et al. (ACS Applied Materials & Interfaces, 2021, 13 (21): 24662-24669) reported a UiO66 grafted with sodium sulfonate (—SO3Na) groups as an electrolyte, which showed 3.6×10 -4 S / cm ionic conductivity. Since MOFs materials themselves have poor electrical conductivity, they often need to be doped or compounded with other materials to improve their ionic conductivity. Secondly, the mechanical properties of MOFs materials are relatively weak, and their structure needs to be optimized during the preparation process to improve their stability and durability. In addition, the preparation method of MOFs-based solid electrolytes also needs further research to achieve a simple and low-cost synthesis process. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a novel method for preparing MOFs-based solid electrolyte.

[0006] In order to solve the above technical problems, the present invention provides a method for preparing a MOFs-based solid electrolyte membrane for a sodium ion battery, comprising the following steps:

[0007] 1) Dissolve the soluble zinc salt in solvent I, add 2-methylimidazole to dissolve, and continue stirring for 1 to 2 hours (to promote the metal ions and organic ligands to form MOFs crystals), and then crystallize;

[0008] The obtained MOFs crystals are washed and baked (to activate the crystal structure and increase its surface area and pore performance) to obtain MOFs particles; the baking is carried out at 90 to 110° C. for 5 to 7 hours;

[0009] The molar ratio of the zinc salt: 2-methylimidazole = 1:1±0.05;

[0010] 2) Add the MOFs particles obtained in step 1) into the ionic liquid solvent and stir until the MOFs particles are evenly dispersed; then separate (centrifuge or filter after standing), resuspend the solid precipitate obtained by separation in acetone, and the obtained suspension is used as the coating liquid;

[0011] The ionic liquid solvent is composed of an ionic liquid and a solvent II;

[0012] 3) The coating liquid is uniformly coated on a pre-cleaned substrate to form a thin film (uniform thin film), and then dried until the acetone in the film is evaporated, and then dried at 60-80°C for 10-12h (to solidify the MOFs structure and the distribution of the ionic liquid), and then treated at 95-105°C for 1.5-2.5h; finally, the film is separated from the substrate to obtain a MOFs-based solid electrolyte membrane (about 0.1-0.2mm).

[0013] The obtained product of the present invention is a MOFs-based solid electrolyte membrane doped with ionic liquid (IL).

[0014] As an improvement to the preparation method of the MOFs-based solid electrolyte membrane of the present invention: the ionic liquid in step 2) is 1-butyl-3-methylimidazolium chloride;

[0015] In the ionic liquid solvent, ionic liquid: solvent II = 10-50 g / 60-100 mL, the solvent II is composed of water and ethanol, and the volume ratio of water: ethanol = 2-3:1;

[0016] An ionic liquid solvent containing 10 to 50 g (preferably 10 to 30 g) of ionic liquid is used for every 1 g of MOFs particles.

[0017] As a further improvement of the method for preparing the MOFs-based solid electrolyte membrane of the present invention: in the step 1), the soluble zinc salt is zinc nitrate or zinc acetate.

[0018] As a further improvement of the preparation method of the MOFs-based solid electrolyte membrane of the present invention: in the step 1), the solvent I is DMF (N,N-dimethylformamide). Generally, 40 to 80 mL of the solvent I is used for every 0.25 mol of the soluble zinc salt.

[0019] As a further improvement of the preparation method of the MOFs-based solid electrolyte membrane of the present invention: in the step 1),

[0020] The reagent used for crystallization is ethanol or acetone;

[0021] The reagent used for washing is ethanol or acetone.

[0022] As a further improvement of the preparation method of the MOFs-based solid electrolyte membrane of the present invention: in the step 1),

[0023] The MOFs crystals are washed and dried (dried to constant weight at room temperature) and then baked.

[0024] As a further improvement of the preparation method of the MOFs-based solid electrolyte membrane of the present invention: in step 1),

[0025] After baking, the mixture is crushed to obtain MOFs particles that can pass through a 100-mesh sieve.

[0026] As a further improvement of the method for preparing the MOFs-based solid electrolyte membrane of the present invention: in step 2), 15 to 25 ml of acetone is used to suspend every 1 g of MOFs particles.

[0027] As a further improvement of the method for preparing the MOFs-based solid electrolyte membrane of the present invention: in step 3), the substrate is a glass substrate or a silicon substrate;

[0028] The substrate is rinsed with acetone, isopropyl alcohol, and deionized water in sequence to obtain a pre-cleaned substrate.

[0029] As a further improvement of the method for preparing the MOFs-based solid electrolyte membrane of the present invention: the coating in step 3) is spin coating, the spin coating speed is set to 400-600 rpm, and the spin coating time is 20-40 seconds.

[0030] The present invention aims to provide a novel method for preparing MOFs-based solid electrolytes, improve the overall performance of sodium-ion batteries through reasonable design and optimization, and provide reliable technical support for the practical application of sodium-ion batteries.

[0031] Existing MOFs-based solid electrolyte membranes usually use MOFs materials as the main framework, which enhances the conductivity of the electrolyte by introducing polymers or doping with inorganic / organic ions. Compared with the prior art, the present invention introduces ionic liquids (ILs) into MOFs-based solid electrolytes to form a new MOFs-based solid electrolyte membrane. This is different from the traditional polymer or sodium salt doping method. Ionic liquids have high ionic conductivity and chemical stability. Unlike traditional electrolytes, ionic liquids have good conductivity in a wide temperature range and are independent of humidity.

[0032] The MOFs-based solid electrolyte of the present invention has the following technical advantages:

[0033] 1) The MOFs structure provides a large number of ion transport channels, and the doping of ionic liquids enhances the ionic conductivity of the electrolyte.

[0034] 2) The high chemical stability of MOFs materials and the protective effect of ionic liquids improve the stability of the composite film during the cycle.

[0035] 3) Ionic liquids generally have lower volatility, which reduces the risk of leakage, improves battery safety, and is environmentally friendly compared to traditional liquid electrolytes. DETAILED DESCRIPTION

[0036] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process.

[0037] Example 1. Preparation method of MOFs-based solid electrolyte membrane

[0038] 1) First, 0.25 mol of zinc nitrate was dissolved in 50 mL of DMF (N,N-dimethylformamide), and then 0.25 mol of 2-methylimidazole was added under stirring conditions. The mixture was stirred at room temperature to dissolve the 2-methylimidazole evenly. The mixture was then stirred at room temperature for about 1 hour to promote the formation of MOFs crystals between metal zinc ions and organic ligands (2-methylimidazole).

[0039] After the reaction was completed, about 100 mL of ethanol was slowly added as a reaction terminator to precipitate and crystallize the MOFs crystals from the solution.

[0040] The precipitated MOFs crystals are washed with ethanol and placed in a ventilated environment or a vacuum drying oven to be completely dried (dried to constant weight at room temperature) to remove a small amount of moisture adsorbed from the air and present in solvents such as ethanol.

[0041] The dried MOFs crystals were baked in an oven at 100°C for 6 hours to activate the crystal structure and increase its surface area and porosity. The baked large-particle MOFs crystals were crushed and passed through a 100-mesh sieve to obtain MOFs particles of uniform size.

[0042] 2) Add 10 g of 1-butyl-3-methylimidazolium chloride (as an ionic liquid) into a solvent consisting of 50 mL of water and 20 mL of ethanol to obtain an ionic liquid solution;

[0043] 1 g of MOFs particles prepared in step 1) were added to the above ionic liquid solvent, and stirred at room temperature for about 1 hour to ensure that the MOFs particles were fully dispersed in the ionic liquid solvent; then centrifuged at 5000 rpm for 10 minutes (or filtered after standing for 4 hours) to separate the solid precipitate (MOF material doped with part of the ionic liquid) and the solvent (water and ethanol). The solid precipitate was resuspended in 20 mL of acetone, and the resulting suspension was used as the coating liquid.

[0044] 3) Using acetone, isopropanol, and deionized water to rinse the glass substrate or silicon substrate in sequence as a pre-cleaned substrate;

[0045] Use a spin coater to evenly coat the coating liquid on the pre-cleaned substrate; the spin coating speed is set to 500rpm and the spin coating time is set to 30 seconds to ensure the formation of a uniform film. Then, place the coated substrate in a ventilated environment or on a heating plate to slowly evaporate the solvent acetone (until no more acetone is evaporated), and then dry it at 80°C for 12h to solidify the MOFs structure and the distribution of the ionic liquid; then place it in an oven at 100°C for 2h. Finally, separate the film from the substrate to obtain a MOFs-based solid electrolyte membrane (about 0.1mm thick).

[0046] Embodiment 2: With respect to Embodiment 1, the following changes are made:

[0047] The amount of ionic liquid (1-butyl-3-methylimidazolium chloride) used was changed from 10 g to 30 g; the rest was the same as in Example 1.

[0048] Embodiment 3, compared with embodiment 1, makes the following changes:

[0049] The amount of ionic liquid (1-butyl-3-methylimidazolium chloride) used was changed from 10 g to 50 g; the rest was the same as in Example 1.

[0050] Embodiment 4: With respect to Embodiment 1, the following changes are made:

[0051] The “drying at 80° C. for 12 h” in step 3) is changed to “drying at 60° C. for 10 h”; the rest is the same as in Example 1.

[0052] Example 5: The "zinc nitrate" in Example 1 is replaced with "zinc acetate", the dosage remains unchanged, still 0.25 mol, and the rest is the same as Example 1.

[0053] Comparative Example 1: The following changes were made relative to Example 1:

[0054] The “ionic liquid (1-butyl-3-methylimidazolium chloride)” was replaced with “ethanol”, and the amount used remained unchanged at 10 g; the rest was the same as in Example 1.

[0055] Comparative Example 2: The following changes were made relative to Example 1:

[0056] The amount of ionic liquid (1-butyl-3-methylimidazolium chloride) used was changed from 10 g to 1 g; the rest was the same as in Example 1.

[0057] Comparative Example 3: The following changes were made relative to Example 1:

[0058] The ionic liquid was changed from "1-butyl-3-methylimidazolium chloride" to "1-ethyl-3-methylimidazolium chloride", and the amount used remained unchanged at 10 g; the rest was the same as in Example 1.

[0059] Comparative Example 4-1, with respect to Example 1, the following changes were made:

[0060] Change “80°C treatment for 12h + 100°C treatment for 2h” to “80°C treatment for 16h”; the rest is the same as Example 1.

[0061] Comparative Example 4-2, with respect to Example 1, the following changes were made:

[0062] The “80°C treatment for 12 h + 100°C treatment for 2 h” is changed to “100°C treatment for 14 h”; the rest is the same as Example 1.

[0063] Comparative Example 5: The following changes were made relative to Example 1:

[0064] The "zinc nitrate" was changed to "copper nitrate", the dosage remained unchanged, still 0.25 mol, and the rest was the same as in Example 1.

[0065] Experiment 1: The electrolyte membranes obtained from all the above embodiments and all the comparative examples are used in sodium ion batteries. The sodium ion battery assembly setting refers to steps 4 and 5 of Example 1 of the invention CN117174988A "A method for preparing lithium / sodium ion battery materials and their application in lithium / sodium ion batteries", and the electrolyte in step 4 is replaced with the MOFs-based solid electrolyte membrane obtained from the above case of the present invention.

[0066] The electrochemical workstation was set to electrochemical impedance spectroscopy (EIS) mode, the frequency range of the EIS measurement was set to 1 Hz to 1 MHz, and a small AC voltage of 10 mV was applied to ensure the accuracy of the measurement while avoiding damage to the electrolyte membrane. Impedance data was collected at room temperature and the charge transfer resistance (R) was calculated, which reflects the resistance to ionic conductivity.

[0067] Ionic conductivity calculation formula:

[0068] Wherein, L is the thickness of the electrolyte membrane (taking Example 1 as an example, about 0.1 mm), R is the resistance of the membrane (obtained from EIS data), and A is the contact area between the cathode / anode and the membrane (2 cm 2 ).

[0069] The results are shown in Table 1 below.

[0070] Experiment 2, stability test:

[0071] The cell assembled in Experiment 1 was connected to an electrochemical workstation and operated at 0.1 mA / cm 2The charge and discharge cycle test was carried out 100 times at a current density of , with the charging voltage range set to 0.01 ~ 2.5V, and the discharging voltage range set to 0 ~ 2.0V. The current, voltage, and power data of each cycle were recorded and the capacity retention rate was calculated.

[0072] Capacity retention rate = discharge capacity at the 100th cycle / initial capacity × 100%.

[0073] Table 1. Application effects of different solid electrolyte films in sodium ion batteries

[0074] Experiment 1 (Ionic conductivity S / cm) Experiment 2 (capacity retention rate %) Example 1 <![CDATA[3.5×10 -3 ]]> 95% Example 2 <![CDATA[4.2×10 -3 ]]> 92% Example 3 <![CDATA[2.8×10 -3 ]]> 90% Example 4 <![CDATA[3.1×10 -3 ]]> 93% Example 5 <![CDATA[3.8×10 -3 ]]> 89% Comparative Example 1 <![CDATA[1.2×10 -4 ]]> 70% Comparative Example 2 <![CDATA[1.5×10 -4 ]]> 65% Comparative Example 3 <![CDATA[1.0×10 -4 ]]> 72% Comparative Example 4-1 <![CDATA[2.0×10 -4 ]]> 60% Comparative Example 4-2 <![CDATA[2.1×10 -4 ]]> 62% Comparative Example 5 <![CDATA[1.8×10 -4 ]]> 68%

[0075] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.

Claims

1. A method for preparing a MOFs-based solid electrolyte membrane for sodium ion batteries, characterized in that The following steps are involved: 1) Dissolve the soluble zinc salt in solvent I, add 2-methylimidazole to dissolve, continue stirring for 1 to 2 hours, and then crystallize; The obtained MOFs crystals are washed and baked to obtain MOFs particles; the baking is performed at 90 to 110° C. for 5 to 7 hours; The molar ratio of the zinc salt: 2-methylimidazole = 1:1±0.05; 2) adding the MOFs particles obtained in step 1) into the ionic liquid solvent and stirring until the MOFs particles are evenly dispersed; then separating and resuspending the solid precipitate obtained by separation in acetone, and the obtained suspension is used as the coating liquid; The ionic liquid solvent is composed of an ionic liquid and a solvent II; 3) The coating liquid is uniformly coated on a pre-cleaned substrate to form a thin film, and then dried until the acetone in the film is evaporated, and then dried at 60-80°C for 10-12h, and then treated at 95-105°C for 1.5-2.5h; finally, the film is separated from the substrate to obtain a MOFs-based solid electrolyte membrane.

2. The method for preparing a MOFs-based solid electrolyte membrane according to claim 1, characterized in that The ionic liquid in step 2) is 1-butyl-3-methylimidazolium chloride; In the ionic liquid solvent, ionic liquid: solvent II = 10-50 g / 60-100 mL, the solvent II is composed of water and ethanol, and the volume ratio of water: ethanol = 2-3:1; An ionic liquid solvent containing 10 to 50 g of ionic liquid is used for every 1 g of MOFs particles.

3. The method for preparing a MOFs-based solid electrolyte membrane according to claim 2, characterized in that In the step 1), the soluble zinc salt is zinc nitrate or zinc acetate.

4. The method for preparing a MOFs-based solid electrolyte membrane according to claim 3, characterized in that In the step 1): Solvent I was DMF.

5. The method for preparing a MOFs-based solid electrolyte membrane according to claim 4, characterized in that In the step 1): The reagent used for crystallization is ethanol or acetone; The reagent used for washing is ethanol or acetone.

6. The method for preparing a MOFs-based solid electrolyte membrane according to claim 5, characterized in that In the step 1): The MOFs crystals are washed, dried, and then baked.

7. The method for preparing a MOFs-based solid electrolyte membrane according to claim 6, characterized in that In the step 1): After baking, the mixture is crushed to obtain MOFs particles that can pass through a 100-mesh sieve.

8. The method for preparing a MOFs-based solid electrolyte membrane according to any one of claims 1 to 7, characterized in that In the step 2), 15-25 ml of acetone is used to suspend every 1 g of MOFs particles.

9. The method for preparing a MOFs-based solid electrolyte membrane according to any one of claims 1 to 8, characterized in that In the step 3), the substrate is a glass substrate or a silicon substrate; The substrate is rinsed with acetone, isopropyl alcohol, and deionized water in sequence to obtain a pre-cleaned substrate.

10. The method for preparing a MOFs-based solid electrolyte membrane according to claim 9, characterized in that: The coating in step 3) is performed by spin coating, the spin coating speed is set to 400-600 rpm, and the spin coating time is 20-40 seconds.

Citation Information

Patent Citations

  • Preparation method of lithium / sodium ion battery material and application of lithium / sodium ion battery material in lithium / sodium ion battery

    CN117174988A

  • Electrolyte, preparation method thereof and sodium ion battery

    CN118248948A

  • composite electrolyte amd a lithum battery including the same

    CN105390743A

  • Preparation method of composite solid electrolyte based on metal organic framework / ionic liquid

    CN111180791A

  • Composite solid electrolyte membrane based on hollow structure MOF, preparation method and application thereof

    CN112670543A